DOT STUDY - BORELLI,T (Tufts Archival Research Center, 2007)
Memorandum within the tobacco industry regarding a Department of Transportation (DOT) study. States that ventilation is poor due to high carbon dioxide levels. Claims that the study's results support the notion that separation of smokers and non-smokers is effective.